THE URGENCY OF LEARNING JAVANESE LOCAL CONTENT AS THE PRESERVATION OF JAVANESE CULTURE IN INDONESI - Atik Dina Nasekha; Mulyana (Proceedings of the International Conference on Education, 2023)
Javanese is one of the regional languages in Indonesia. But in fact, the use of the Javanese language is currently experiencing a decline and shift. This requires conservation efforts so that regional languages do not become extinct. The purpose of this study is to describe: (1) Factors causing the shift in the Javanese language, (2) Ways to deal with the fading of the Javanese language, and (3) The role of schools in preserving the Javanese language. This type of research is qualitative descriptive research. Data collection techniques using observation techniques, interviews, and documentation. Sources of research data are journals, informants, and events in which Javanese language learning takes place at school. Data analysis techniques using descriptive analysis techniques and document analysis. The results of the study show that there are several reasons why the Javanese language has begun to fade, such as the globalization of technology, the habits of students who use Indonesian more often, language interference, and the notion that Javanese is an ancient language. The way to overcome this is by getting used to the Javanese language in the family and community environment, holding competitions related to the Javanese language, and learning Javanese at school. The school’s role in maintaining the Javanese language includes carrying out Javanese language learning with innovative learning methods and media, setting aside one day a week to communicate using only the Javanese language, holding Javanese language competitions, and having extracurricular activities regarding Javanese culture. It can be concluded that learning Javanese local content in schools plays a vital role in maintaining Javanese so that one element of Javanese culture, namely language, is maintained.